Education and Youth Employment in Urban Peru - Garavito, Cecilia (2015)
The objective of this paper is to analyze which variables determine that young people who still live with their parents study, work, combine both activities or stay away from them. We are interested in what is it that keeps young people in the educative system, even if they are working, and if there are differences related to gender roles. We work with a model of efficient cooperative negotiation between parents and the son or daughter, and estimate a Multinomial Logit regression with data for urban Peru in the year 2014. We find that young people will stay in the educative system, even if they are working, when their negotiation power at home is high, when their opportunity cost is low, and when their parents have a higher level of education.